2022
DOI: 10.1039/d1cp04920h
|View full text |Cite
|
Sign up to set email alerts
|

A facile surface alloy-engineering route to enable robust lithium metal anodes

Abstract: The Li-rich alloy has been developed as the advanced artificial SEI layer to suppress the formation of Li dendrite and parasitic reactions on the Li metal anode. Here, we systematically...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Young et al also adopted AIMD simulations, and they found that EC broke down more quickly on Li and Ca surfaces than on Al because the charge transfer is in a larger amount and at a much faster pace on Li and Ca owing to their lower electronegativity and ionization energies . Electrode surface treatment and electrode engineering are effective approaches to passivating such anode surfaces and dampening their high reactivities. ,, The Li-rich alloys, including LiCu, LiGa, LiMg, and LiZn, were investigated regarding their ability to suppress the electrolyte decomposition compared with Li metal anodes. The electron transfer between the anode and electrolyte molecules is efficiently reduced when adopting these alloy systems, especially LiGa, demonstrating their robust stability against electrolytes …”
Section: Electrode–electrolyte Interfacial Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Young et al also adopted AIMD simulations, and they found that EC broke down more quickly on Li and Ca surfaces than on Al because the charge transfer is in a larger amount and at a much faster pace on Li and Ca owing to their lower electronegativity and ionization energies . Electrode surface treatment and electrode engineering are effective approaches to passivating such anode surfaces and dampening their high reactivities. ,, The Li-rich alloys, including LiCu, LiGa, LiMg, and LiZn, were investigated regarding their ability to suppress the electrolyte decomposition compared with Li metal anodes. The electron transfer between the anode and electrolyte molecules is efficiently reduced when adopting these alloy systems, especially LiGa, demonstrating their robust stability against electrolytes …”
Section: Electrode–electrolyte Interfacial Reactionsmentioning
confidence: 99%
“…Electrode surface treatment and electrode engineering are effective approaches to passivating such anode surfaces and dampening their high reactivities. ,, The Li-rich alloys, including LiCu, LiGa, LiMg, and LiZn, were investigated regarding their ability to suppress the electrolyte decomposition compared with Li metal anodes. The electron transfer between the anode and electrolyte molecules is efficiently reduced when adopting these alloy systems, especially LiGa, demonstrating their robust stability against electrolytes …”
Section: Electrode–electrolyte Interfacial Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is interesting since most of Li alloys possess higher Li diffusion coefficient than pure lithium, which contributes to enhanced electrochemical kinetics and reduces the dendrites growth [51] . In addition, Li‐rich alloys limit the parasitic reactions between the anode and the electrolyte [52] and could be more air‐stable than pure lithium facilitating their manipulation and storage in dry room [53] . Several metals to date have been sputtered on Li metal such as Al, [53] Si, [54] Cu, [55] Au [56] and Zn [56,57] …”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of the LLMB, we can borrow two main ideas from the LMB strategy. One is to homogenize the nucleation process of lithium in the anode, and the other is to optimize the SEI layer. For the nucleation process of lithium, lithiophilic substrates such as Li–Au, , Li–Ag, , and Li–Zn , alloys are often used to reduce the nucleation overpotential of lithium and thus achieve homogeneous deposition. Huang et al used Au-modified Cu foil as a current collector and paired it with a Li 2 S cathode to construct AFLMB with a very high energy density up to 626 W kg –1 .…”
Section: Introductionmentioning
confidence: 99%